Evaluasi Pembelajaran Pendidikan Agama Islam Berbasis Tiga Ranah Komprehensif Di SMA Negeri 1 Bengkalis - Suci Rahmawati; Nisa Afrawasih; Vera Santika; Siti Khairiah (JURNAL MANAJEMEN PENDIDIKAN, 2026)
EVALUATION OF ISLAMIC RELIGIOUS EDUCATION LEARNING BASED ON THREE COMPREHENSIVE DOMAINS AT STATE SENIOR HIGH SCHOOL 1 BENGKALIS Learning evaluation is a vital component that determines the success of transforming religious values in Islamic Religious Education (PAI). This study aims to analyze in depth and describe the implementation of PAI learning evaluation at SMAN 1 Bengkalis, which covers three main domains of student development, namely cognitive, affective, and psychomotor domains, as well as to identify the constraints faced by teachers and their resolution efforts. The research approach used is descriptive qualitative with a case study method through mini-research techniques. Data collection was carried out through participatory observation, in-depth interviews with the PAI teacher (Mrs. Rina Mutiara, S.Pd) and three students of class XI.6, and documentation studies of curriculum, lesson plans, and assessment sheets. Data analysis was conducted interactively, including data reduction, data display, and drawing conclusions/verification of validity through source and technique triangulation. The research results indicate that: (1) The evaluation of the cognitive aspect at SMAN 1 Bengkalis has been structured through diagnostic, formative, and summative assessments with variations of written tests, questions and answers, and discussions; (2) The evaluation of the affective aspect uses daily behavior observation and standardized attitude assessment rubric instruments, where teachers actively act as role models (uswatun hasanah); (3) The evaluation of the psychomotor aspect is carried out through real practical activities based on essential materials such as role-playing on the concepts of sincerity, asceticism (zuhud), and modesty (malu), complemented by joint reflection. The main constraints identified include the heterogeneity of students' comprehension abilities, the complexity of typical-inclusive affective assessment, limited linear time allocation in the classroom, and the dominance of traditional paper-based tests. The resolution efforts involve differentiation of individual approaches, utilization of multi-scale assessment rubrics, variation of contextual methods, and provision of constructive-evaluative feedback continuously.